Community Compliance in Implementing 5M COVID-19 Prevention in Kampung Tengari, Praya City - Widya Ariani; Sulistyawati Sulistyawati; Tiara Lintang Sari (Universitas Ahmad Dahlan, 2023)
Background: COVID-19 is a disease caused by the SARS-CoV-2 virus, which has spread worldwide. Many people need to be made aware of the risks of COVID-19 transmission and the advantages of implementing the 5M health protocol. People's disobedience is a daily occurrence that is accepted in the environment. This noncompliance has accelerated the spread of the virus, increasing the number of positive citizens and the death toll. This research aims to calculate the main health issues that should be prioritized. Method: This community diagnosis used the Hanlon method, which employed a descriptive study design with a quantitative approach. The total sampling technique was used to determine the sample size of 78 people. Results: The issue in RT 07 Kampung Tengari, Praya City, is that many people still need to be more compliant in implementing the 5M COVID-19 prevention strategy. Conclusion: Implementing the 5M strategy within society is currently at a moderate level and requires further education or counseling to enhance compliance.